Accelerating the prevention of HIV and violence in adolescent girls and young women in Zimbabwe through multi-sectoral programming: Cross-sectional analysis of the 2017 violence against children survey - Martina Mchenga; Brendan Maughan-Brown; Rachel Yates; Lucas Hertzog; Boladé Hamed Banougnin; Silinganisiwe Dzumbunu; Madison T. Little; Lucie Cluver; Elona Toska (Global Public Health, 2025)
In Zimbabwe, adolescent girls and young women (AGYW) encounter significant challenges, including HIV risk and gender-based violence. This study analyses data from 7,211 AGYW aged 13–24 from the 2017 Zimbabwe Violence Against Children Survey. Using a multivariable logistic regression model, it examines the associations between three protective factors: positive parenting, food security, and equitable-gender attitudes and 12 outcomes. Westfall-Young stepdown procedure was used to adjust for multiple hypothesis testing. Percentage predicted probabilities of each outcome occurring in several scenarios were computed: exposure to each protective factor alone or in combination, with other variables kept constant. The findings reveal that equitable-gender attitudes inversely correlate with ten adverse outcomes, including inconsistent condom use (aOR: 0.47) and adolescent pregnancy (aOR: 0.65). Positive parenting also reduce the likelihood of sexual abuse (aOR: 0.63) and physical intimate partner violence (IPV) (aOR: 0.56). Food security is linked to lower odds of physical IPV (aOR: 0.52) and mental distress (aOR: 0.58). The combination of these protective factors demonstrates additive effects across various outcomes. These results suggest that integrating HIV-centered interventions with structural, societal, and relational strategies such as improving food security and promoting equitable gender attitudes could enhance the well-being of AGYW in Zimbabwe.